Synergistic Effect of Nano-Sliver with Sucrose on Extending Vase Life of the Carnation cv. Edun - Park, Da Y.; Naing, Aung H.; Ai, Trinh N.; Han, Jeung-Sul; Kang, In-Kyu; Kim, Chang K. (Frontiers in Plant Science, 2017)
We investigated the effects of sucrose and Nano-silver (NAg) on extending the vase life of cut carnation flowers ‘Edun’. Sucrose suppressed ethylene production by downregulating the genes that code for its biosynthesis. Relative to the control, however, sucrose significantly increased bacterial proliferation on cut stem surfaces and reduced relative fresh weight (RFW), antioxidant activity, and cysteine proteinase inhibitor gene (DcCPi) expression. Consequently, the sucrose-treated flowers had shorter vase lives than the control. In contrast, NAg suppressed ethylene production in the petal, prevented bacterial blockage in the cut stem surface, and improved all the aforementioned parameters. Therefore, NAg increased flower longevity. The most effective treatment in terms of longevity extension and parameter improvement, however, was the combination of NAg and sucrose. These results suggest that sucrose can suppress ethylene production but does not necessarily extend the vase life of the flower cultivar, which is partially or totally insensitive to ethylene. The role of NAg in increasing cut carnation longevity is mainly to inhibit xylem blockage rather than suppress ethylene production, and the combined effect of NAg and sucrose is most effective at prolonging cut carnation vase life, likely due to their synergetic effects on multiple modes of action.